1992
DOI: 10.1007/bf00319630
|View full text |Cite
|
Sign up to set email alerts
|

A novel neuropeptide, pituitary adenylate cyclase-activating polypeptide (PACAP), in human intestine: evidence for reduced content in Hirschsprung's disease

Abstract: A novel neuropeptide, pituitary adenylate cyclase-activating polypeptide (PACAP), exhibits sequence homology with vasoactive intestinal polypeptide (VIP) and occurs in the mammalian brain, lung and gut. The distribution of PACAP in ganglionic and aganglionic portions of the large intestine of patients with Hirschsprung's disease was examined by immunohistochemistry and radioimmunoassay. PACAP-immunoreactive nerve fibers were distributed in all layers of the ganglionic and aganglionic segments of the intestine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 31 publications
3
30
0
Order By: Relevance
“…The presence of PACAP-immunoreactive cell bodies has been observed in the myenteric ganglia throughout the gastrointestinal tract, and the existence of intrinsic neurons has been confirmed by in situ hybridization (Shen et al, 1992;Hannibal et al, 1998). Numerous PACAP-containing nerve fibers have been visualized along the circular muscle fibers and in the longitudinal smooth muscle layer of the esophagus (Uddman et al, 1991a;Köves et al, 1993;Olsson and Holmgren, 1994).…”
Section: F Distribution Of Pituitary Adenylate Cyclaseactivating Polmentioning
confidence: 85%
“…The presence of PACAP-immunoreactive cell bodies has been observed in the myenteric ganglia throughout the gastrointestinal tract, and the existence of intrinsic neurons has been confirmed by in situ hybridization (Shen et al, 1992;Hannibal et al, 1998). Numerous PACAP-containing nerve fibers have been visualized along the circular muscle fibers and in the longitudinal smooth muscle layer of the esophagus (Uddman et al, 1991a;Köves et al, 1993;Olsson and Holmgren, 1994).…”
Section: F Distribution Of Pituitary Adenylate Cyclaseactivating Polmentioning
confidence: 85%
“…Neurotransmission is mediated not only by the "classical" neurotransmitters but also by neuropeptide transmitters like somatostatin (SRIF), substance P (SP), neurotensin, gastrin, cholecystokinin (CCK), neuropeptide Y (NPY), gastrin-releasing peptide (GRP), vasoactive intestinal peptide (VIP) and pituitary adenylate cyclase-activating peptide (PACAP) (Furness et al 1992;McConalogue and Furness 1994;Schultzberg et al 1980). These neuropeptides have been identified with immunohistochemical methods in the enteric nervous system in rats and guinea-pigs (Ekblad et al 1988;Hökfelt et al 2001;Larsson and Sundler 1990;Shen et al 1992), and shown to interact with many specific targets like the smooth muscles, the vessels, the mucosa and the lymphoid tissues. They act on the regulation of gut motility, blood flow, secretion and nutrient absorption as well as on the modulation of the immune response (McConalogue and Furness 1994).…”
Section: Introductionmentioning
confidence: 97%
“…PACAP has been shown to exhibit a protective role against the neuronal toxicity of the gp120 envelope protein of the human immunodeficiency virus suggesting its role as a neurotrophic factor (8). In the human gastrointestinal tract, PACAP may modulate smooth muscle motility as evidenced by a reduction in immunoreactive PACAP nerve fibers in Hirshsprung's disease (9). Type 1 PACAP receptors have also been described on the human lung carcinoma cell lines NCI-H345 and NCI-N417 and the human neuroblastoma cell line NB-OK-1, where they stimulate clonal growth (10,11).…”
mentioning
confidence: 99%